Agency and professional identity among mobile teachers: how does the experience of teaching abroad shape teachers' professional identity?. (18th August 2022) - Rosenfeld, Itamar; Yemini, Miri; Mamlok, Dan
ABSTRACT: In the context of global mobility research, this study explores agency and identity formation among mid-career teachers who travel abroad to experience teaching in a new country. We conducted in-depth interviews with 16 Israeli teachers and examined their retrospective narratives of their teaching experience. Our findings reveal a complex nexus of identity and agency, whereby identity formation echoes agency choices. We conceptualise forms of agency and point to possible connections between agency types and their use in identity formation. We conclude that under circumstances of rapid change, agency plays an important role in identity formation.